Laparoscopic Adjustable Gastric Banding Connecting Tube Causing Small Bowel Obstruction and Perforation - Hashemzadeh, Mojtaba (Hindawi Publishing Corporation, 2013)
Background. Laparoscopic adjustable gastric banding (LAGB) is an effective method of reducing excess weight in obese patients. We report a patient who developed a bowel obstruction caused by the connecting tube between the gastric band and the injection port. Case Presentation. The patient was a 42-year-old Caucasian female who had undergone LAGB 19 months earlier. She presented with dehydration, low-grade fever, tachycardia, and mild abdominal tenderness. Laparotomy revealed that the connecting tube was looped around the mesentery, and a loop of small bowel was incarcerated between the tube and the mesentery. The incarcerated small bowel loop was perforated in two places. Conclusion. Surgeons should be aware of the possibility of obstruction caused by the connecting tube in patients who have undergone LAGB.